Both coiling and clipping induce the time-dependent release of endogenous neuropeptide Y into serum - Bründl, Elisabeth; Proescholdt, Martin; Schödel, Petra; Rosengarth, Katharina; Störr, Eva-Maria; Bele, Sylvia; Kieninger, Martin; Malsy, Manuela; Schmidt, Nils Ole; Schebesch, Karl-Michael (Frontiers in Neurology, 2024)
Background The vaso- and psychoactive endogenous Neuropeptide Y (NPY) has repeatedly been shown to be excessively released after subarachnoid hemorrhage and in numerous psychiatric disorders. NPY is stored in sympathetic perivascular nerve fibers around the major cerebral arteries. This prospective study was designed to analyze the impact of microsurgical and endovascular manipulation of the cerebral vasculature versus cranio- and durotomy alone on the serum levels of NPY. Methods 58 patients (drop-out n = 3; m:f = 26:29; mean age 52.0 ± 14.1 years) were prospectively enrolled. The vascular group underwent repair for unruptured intracranial aneurysms (UIA) of the anterior circulation [endovascular aneurysm occlusion (EV) n = 13; microsurgical clipping (MS) n = 17]; in the non-vascular group, 14 patients received microsurgical resection of a small-sized convexity meningioma (CM), and 11 patients with surgically treated degenerative lumbar spine disease (LD) served as control. Plasma was drawn (1) before treatment (t0), (2) periprocedurally (t1), (3) 6 h postprocedurally (t2), (4) 72 h postprocedurally (t3), and (5) at the 6-week follow-up (FU; t4) to determine the NPY levels via competitive enzyme immunoassay in duplicate serum samples. We statistically evaluated differences between groups by calculating one-way ANOVA and for changes along the time points using repeated measure ANOVA. Results Except for time point t0, the serum concentrations of NPY ranged significantly higher in the vascular than in the non-vascular group (p < 0.001), with a slight decrease in both vascular subgroups 6 h postprocedurally, followed by a gradual increase above baseline levels until FU. At t3, the EV subgroup showed significantly higher NPY levels (mean ± standard deviation) than the MS subgroup (0.569 ± 0.198 ng/mL vs. 0.415 ± 0.192 ng/mL, p = 0.0217). The highest NPY concentrations were measured in the EV subgroup at t1, t3, and t4, reaching a climax at FU (0.551 ± 0.304 ng/mL). Conclusion Our study reveals a first insight into the short-term dynamics of the serum levels of endogenous NPY in neurosurgical and endovascular procedures, respectively: Direct manipulation within but also next to the major cerebral arteries induces an excessive release of NPY into the serum. Our findings raise the interesting question of the potential capacity of NPY in modulating the psycho-behavioral outcome of neurovascular patients.